2016
DOI: 10.1002/cncr.30228
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of vaginal brachytherapy is associated with improved survival in women with stage I endometrioid adenocarcinoma of the uterus: A National Cancer Data Base study

Abstract: Analyses of this large database support the utility of postoperative VB for many women with stage I endometrial cancer. Unfortunately, RT appears to be underused in this population. Greater adherence to consensus guidelines may lead to improved outcomes. Cancer 2016;122:3724-31. © 2016 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 24 publications
1
17
0
1
Order By: Relevance
“…Interestingly, CTNNB1 and TP53 were not only both associated with recurrence-free survival, but had significantly elevated hazard ratios on par with those seen with tumor grade in prior studies of early stage endometrial cancers (5, 9). We suspect the reason that myometrial invasion, lymphatic/vascular invasion, and tumor size were not independent predictors in this retrospective cohort may have been related to common adjuvant treatment decision-making strategies within this retrospective cohort, as providers may have already taken these variables into account and thereby decreased these patients’ risks for recurrence.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Interestingly, CTNNB1 and TP53 were not only both associated with recurrence-free survival, but had significantly elevated hazard ratios on par with those seen with tumor grade in prior studies of early stage endometrial cancers (5, 9). We suspect the reason that myometrial invasion, lymphatic/vascular invasion, and tumor size were not independent predictors in this retrospective cohort may have been related to common adjuvant treatment decision-making strategies within this retrospective cohort, as providers may have already taken these variables into account and thereby decreased these patients’ risks for recurrence.…”
Section: Discussionmentioning
confidence: 78%
“…Both criteria have been implemented in subsequent clinical trials and are used in clinical practice. However, despite these and other proposed algorithms (69), the appropriate criteria for allocating early endometrial cancer patients to adjuvant treatment remains uncertain. Balancing concerns about over-treatment with the reality that recurrences still occur in this population and are largely incurable reinforces the need for better risk-prediction strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Seventy-two percent of endometrial cancers are detected at stage I, whereas 3% are detected at stage III (Sorosky, 2012). According to an analysis from the National Cancer Database, vaginal brachytherapy (VBT) is the most common adjuvant treatment for early-stage endometrial cancer, and its use has been increasing (Rydzewski et al, 2016). VBT is a form of radiation therapy that involves the insertion of a cylindrical applicator containing radioactive material into the vagina at varying lengths, durations, and radiation doses, depending on the cancer stage (ACS, 2016b;Small et al, 2012).…”
mentioning
confidence: 99%
“…In this study, when the landmark time was implemented, the benefit of PORT in N2 lung cancer was no longer apparent. 23 Although many of the manuscripts in this study that adjusted for ITB did find a benefit of PORT, in a similar 53 LM 3 2017 Endometrial cancer 54 No NA 2016 Gastric cancer 55 No NA 2017 Salivary cancer 56 LM 6 2019 Ampullary cancer 57 LM 3 2018 Bladder cancer 58 LM 1 2019 Mesothelioma 59 No NA 2019 Oral cavity 60 No NA 2019 Salivary cancer 61 No manner to the Herskovic et al study, they may not have found as large of a magnitude of benefit or PORT may have lost significance if the LM was chosen at a later time point. Furthermore, the LM times were often accompanied with a lack of explanation, and greater detail could have contextualized the results more precisely, especially with relation to disease histologies and, in some cases, overall treatment paradigms.…”
Section: Discussionmentioning
confidence: 69%